Impact of number elements on array factor in linear arrays antenna - Siti Fazlina, Maharimi; Mohd Faizal, Jamlos, Dr.; Mohd. Fareq, Abd. Malek, Dr.; Neoh, Siew Chin, Dr (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org